Technologie výroby dveří kolejových vozidel pomocí nových lepících systémů - Tesař, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Diplomová práce se zabývá lepícím procesem, který je dominantní technologií při výrobě dveřních křídel kolejových vozidel. Po nezbytném prostudování základní podstaty lepených spojů jsou dále představeny konstrukční možnosti tohoto výrobku. Stěžejní části práce je prezentace dosažených výsledků zkoušek jednotlivých vybraných typů lepidel. Na základě těchto výsledků je vybrán nejvhodnější typ a dodavatel průmyslového lepidla.

This master´s thesis deals with the bonding process, which is the dominant technology of the production of door leaves for railway vehicles. Following the necessary study of the basic essence of bonded joints the thesis further introduces the individual construction options of this product. The essential part of the thesis is represented by presentation of the achieved results of the testing of individual selected types of adhesives. On the basis of these results the most suitable type and supplier of industrial adhesive is selected.
Manufacturing technology of rail vehicle by new adhesive systems
Keywords: Lepení; technologie lepení; dveřní křídla; zkoušky; napětí; rám; hliníkové profily.; Bonding; technology of bonding; door leaves; testing; shear stress; frame; aluminium profiles.